2021
DOI: 10.1073/pnas.2026183118
|View full text |Cite
|
Sign up to set email alerts
|

Use of NAD tagSeq II to identify growth phase-dependent alterations in E. coli RNA NAD + capping

Abstract: Recent findings regarding nicotinamide adenine dinucleotide (NAD+)-capped RNAs (NAD-RNAs) indicate that prokaryotes and eukaryotes employ noncanonical RNA capping to regulate gene expression. Two methods for transcriptome-wide analysis of NAD-RNAs, NAD captureSeq and NAD tagSeq, are based on copper-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry to label NAD-RNAs. However, copper ions can fragment/degrade RNA, interfering with the analyses. Here we report development of NAD tagSeq II, which uses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 45 publications
(102 reference statements)
3
45
0
Order By: Relevance
“…149 Another way is to identify NAD-capped RNA from organelles or prokaryotic cells. 154 One problem that still needed to be resolved was to add poly(A) tails to the RNA before preparing ONT DRS libraries, as Zhang et al did. 154 The Innovation 2, 100153, November 28, 2021 www.cell.com/the-innovation…”
Section: Ont Drs and Its Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…149 Another way is to identify NAD-capped RNA from organelles or prokaryotic cells. 154 One problem that still needed to be resolved was to add poly(A) tails to the RNA before preparing ONT DRS libraries, as Zhang et al did. 154 The Innovation 2, 100153, November 28, 2021 www.cell.com/the-innovation…”
Section: Ont Drs and Its Applicationsmentioning
confidence: 99%
“…51 One way to resolve the problem is to ligate an RNA adapter to the 5 0 end of the sequenced RNAs, as was done for NAD-capped RNA with the TagSeq method. 151,154,164 The relatively higher base error rate, especially in the low-complexity genomic regions, has long prevented genetic testing and microbial detection from utilizing the full power of ONT DDS. However, the miniaturization of equipment and fast turnaround time provide hope that the two applications will become more approachable.…”
Section: Challenges For Ont Dds and Drsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, NAD tagSeqII—a combination of NAD tagSeq and SPAAC‐NAD‐Seq—recently identified that NAD‐capping in E. coli is dependent on its growth phases. [ 116 ]…”
Section: ′‐Terminal Rna Modificationsmentioning
confidence: 99%